Distribution of LPXRFa, a gonadotropin‐inhibitory hormone ortholog peptide, and LPXRFa receptor in the brain and pituitary of the tilapia. Issue 14 (7th March 2016) - Ogawa, Satoshi; Sivalingam, Mageswary; Biran, Jakob; Golan, Matan; Anthonysamy, Rachel Shalini; Levavi‐Sivan, Berta; Parhar, Ishwar S.
ABSTRACT: In vertebrates, gonadotropin‐releasing hormone (GnRH) and gonadotropin‐inhibitory hormone (GnIH), respectively, regulate reproduction in positive and negative manners. GnIH belongs to the LPXRFa family of peptides previously identified in mammalian and nonmammalian vertebrates. Studying the detailed distribution of LPXRFa as well as its receptor (LPXRFa‐R) in the brain and pituitary is important for understanding their multiple action sites and potential functions. However, the distribution of LPXRFa and LPXRFa‐R has not been studied in teleost species, partially because of the lack of fish‐specific antibodies. Therefore, in the present study, we generated specific antibodies against LPXRFa and its receptor from Nile tilapia ( Oreochromis niloticus ), and examined their distributions in the brain and pituitary by immunohistochemistry. Tilapia LPXRFa‐immunoreactive neurons lie in the posterior ventricular nucleus of the caudal preoptic area, whereas LPXRFa‐R‐immunoreactive cells are distributed widely. Double immunofluorescence showed that neither LPXRFa‐immunoreactive fibers nor LPXRFa‐R is closely associated or coexpressed with GnRH1, GnRH3, or kisspeptin (Kiss2) neurons. In the pituitary, LPXRFa fibers are closely associated with gonadotropic endocrine cells [expressing luteinizing hormone (LH) and follicle‐stimulating hormone (FSH)], with adrenocorticomelanotropic cells [corticotropin (ACTH) and α‐melanotropin (α‐MSH)], and with somatolactin endocrine cells. In contrast, LPXRFa‐R are expressed only in LH, ACTH, and α‐MSH cells. These results suggest that LPXRFa and LPXRFa‐R signaling acts directly on the pituitary cells independent from GnRH or kisspeptin and could play multiple roles in reproductive and nonreproductive functions in teleosts. J. Comp. Neurol. 524:2753–2775, 2016. © 2016 Wiley Periodicals, Inc. Abstract : LPXRFa and LPXRFa‐R signaling (green) acts directly on pituitary endocrine cells independently of gonadotropin‐releasing hormone (GnRH1, red) or kisspeptin (Kiss2, blue) neurons and could play multiple roles in reproductive and nonreproduction in teleosts.